PEMETAAN KONDISI PERPUSTAKAAN POLITEKNIK NEGERI BANDUNG BERDASARKAN PEDOMAN STANDAR AKREDITASI PERPUSTAKAAN NASIONAL - Purwanti, Helmi; Gemalia, Idayu (Edulib, 2018)
Library as one of the supporting units in college must provide good services to its customers. Therefore, a library must comply with the laws, regulations, and standards that have been made. Three institutions creating the standards of college libraries for improving the services are Standar Nasional Indonesia (SNI), Perpustakaan Nasional Republik Indonesia (PNRI), and Direktorat Jendral Pendidikan Tinggi (DIKTI). Among those three institutions, PNRI should be as a reference since its assessment has the most details. Politeknik Negeri Bandung (Polban) as higher education that has been established for more than 20 years should meet PNRI standard. This study used the descriptive method to describe the condition of the library associated with   the   nine   components   in   the   accreditation guidelines which are Service, Cooperation, Collection, Organization of Library Material, Human Resources, Infrastructure Building/Room, Budget, Library Management, and Library Collection Care. The   data   was   obtained   through interviews, observation based on nine components of PNRI standard, and document analysis with the solutions. The results from this research show that Polban Library has met the two components of the nine components that are Organization of Library Material and Library Collection Care. This is because the library has implemented its activities in accordance with the guidance of the University Library Accreditation Standard set by National Library of Indonesia (SNI). Meanwhile, the other seven components have not been met yet by Polban. They need to be fixed and adjusted to the prevailing standards.